A Neo-Fatimid Treasury of Books Arabic Manuscripts among the Alawi Bohras of South Asia - Akkerman, Olly (Edinburgh University Press, 2023)
This book tells the story of a manuscript repository found all over the pre-modern Muslim world: the khizanat al-kutub, or treasury of books. The focus is on the undisclosed Arabic manuscript culture of a small but vibrant South Asian Shi'i Muslim community, the Bohras. It looks at how books that were once part of one of the biggest imperial book repositories of the medieval Muslim world, the khizanat of the Fatimids of North Africa and Egypt (909CE-1171CE) ended up having a rich social life among the Bohras across the Western Indian Ocean, starting in Yemen and ending in Gujarat. It shows how, under strict conditions of secrecy, and over several centuries, one khizana was turned into another, its manuscripts gaining new meanings in the new social realities in which they were preserved, read, transmitted, venerated and copied into. What emerged was a new distinctive Bohra Ismaili manuscript culture shaped by its local contexts.